Implementasi P5 (Proyek Penguatan Profil Pelajar Pancasila) Dalam Mewujudkan Visi Misi Kurikulum Merdeka Belajar di MAN 2 Bone - Ismail; Arni Anti Kinas (JURNAL MAPPESONA, 2025)
Research This research aims to comprehensively describe the implementation of the Pancasila Student Profile Strengthening Project (P5) as part of the independent learning curriculum at MAN 2 Bone, as well as how the project contributes to realizing the vision and mission of education oriented towards character building, strengthening 21st century competencies, and student-centered learning. The Independent Curriculum developed by the Ministry of Education and Culture emphasizes the importance of contextual learning that fosters Pancasila values, creativity, mutual cooperation, and independence through real project activities relevant to students' daily lives. The research method used is qualitative research through a psychological and management approach. The data collection techniques used were interviews, observations, and documentation taken from primary and secondary data sources. The data analysis techniques used were data reduction, data presentation, and data conclusion. The results of this study indicate that 1) the implementation of P5 at MAN 2 Bone has a positive impact on shaping student character. Religious values such as faith and piety are instilled through activities such as recitation and congregational prayers, while social values such as mutual cooperation, tolerance, and independence are built through collaborative projects themed around local wisdom, stopping bullying, entrepreneurship, and sustainable living. 2) The vision and mission of the Merdeka Curriculum at MAN 2 Bone show progress in implementing the student-centered Merdeka Curriculum. Learning is student-centered, active, and contextual. Collaboration among all elements of the school ensures that the Merdeka Curriculum is not only implemented but also internalized as a joint effort to realize the project of strengthening the Pancasila student profile (P5).